Distance decay in delivery care utilisation associated with neonatal mortality. A case referent study in northern Vietnam - Eriksson Leif; Do Tran T; Sohel Nazmul; Målqvist Mats; Persson Lars-Åke (BMC, 2010)
Abstract Background Efforts to reduce neonatal mortality are essential if the Millennium Development Goal (MDG) 4 is to be met. The impact of spatial dimensions of neonatal survival has not been thoroughly investigated even though access to good quality delivery care is considered to be one of the main priorities when trying to reduce neonatal mortality. This study examined the association between distance from the mother's home to the closest health facility and neonatal mortality, and investigated the influence of distance on patterns of perinatal health care utilisation. Methods A surveillance system of live births and neonatal deaths was set up in eight districts of Quang Ninh province, Vietnam, from July 2008 to December 2009. Case referent design including all neonatal deaths and randomly selected newborn referents from the same population. Interviews were performed with mothers of all subjects and GIS coordinates for mothers' homes and all health facilities in the study area were obtained. Straight-line distances were calculated using ArcGIS software. Results A total of 197 neonatal deaths and 11 708 births were registered and 686 referents selected. Health care utilisation prior to and at delivery varied with distance to the health facility. Mothers living farthest away (4th and 5th quintile, ≥1257 meters) from a health facility had an increased risk of neonatal mortality (OR 1.96, 95% CI 1.40 - 2.75, adjusted for maternal age at delivery and marital status). When stratified for socio-economic factors there was an increased risk for neonatal mortality for mothers with low education and from poor households who lived farther away from a health facility. Mothers who delivered at home had more than twice as long to a health facility compared to mothers who delivered at a health care facility. There was no difference in age at death when comparing neonates born at home or health facility deliveries (p = 0.56). Conclusion Distance to the closest health facility was negatively associated with neonatal mortality risk. Health care utilisation in the prenatal period could partly explain this risk elevation since there was a distance decay in health system usage prior to and at delivery. The geographical dimension must be taken into consideration when planning interventions for improved neonatal survival, especially when targeting socio-economically disadvantaged groups.